2013
DOI: 10.1002/jmri.24361
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between tissue metabolism and cellularity assessed by standardized uptake value and apparent diffusion coefficient in peritoneal metastasis

Abstract: There was a significant inverse correlation between SUV and ADC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…21,22 Many studies have also shown an inverse correlation between SUV max and ADC min in various types of cancers, including nonsmall-cell lung cancer, rectal cancer, gastrointestinal stromal tumor, cervical cancer, and endometrial cancer. 6,[11][12][13][14][15][16][17][18][19] A study reported by Nakamura et al 6 showed a strong inverse correlation (r 5 -0.677; P < 0.001) between SUV max derived from PET/CT and ADC min derived from MRI of primary tumors in 131 patients with endometrial cancer. Although the different principles of attenuation correction in PET/CT and PET/MR 23,24 may result in discrepancies in SUV measurements, several studies have shown a high correlation between SUV derived from PET/ CT and PET/MR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22 Many studies have also shown an inverse correlation between SUV max and ADC min in various types of cancers, including nonsmall-cell lung cancer, rectal cancer, gastrointestinal stromal tumor, cervical cancer, and endometrial cancer. 6,[11][12][13][14][15][16][17][18][19] A study reported by Nakamura et al 6 showed a strong inverse correlation (r 5 -0.677; P < 0.001) between SUV max derived from PET/CT and ADC min derived from MRI of primary tumors in 131 patients with endometrial cancer. Although the different principles of attenuation correction in PET/CT and PET/MR 23,24 may result in discrepancies in SUV measurements, several studies have shown a high correlation between SUV derived from PET/ CT and PET/MR.…”
Section: Discussionmentioning
confidence: 99%
“…Results of previous studies have shown an inverse correlation between SUV max derived from PET/CT and ADC min derived from MRI in various types of cancers, including endometrial cancer . The recently introduced integrated PET/MR system has provided a platform for simultaneous multiparametric imaging, with reduced misregistration artifacts and possible physiologic changes during the time interval between PET and MRI examinations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical utilisation of functional imaging in gynaecological malignancy is evolving [ 2 4 ]. In the era of more sophisticated treatment options such as image-guided adaptive radiotherapy, functional imaging techniques such as diffusion-weighted MRI (DW-MRI) and 18 F–fluoro-deoxyglucose positron emission tomography integrated with computed tomography (FDG PET/CT) have been demonstrated to provide information for more precise definition of radiation target [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…ADVANCED IMAGING TECHNIQUES are increasingly applied in the evaluation of gynecological cancers . Emerging evidence suggests that diffusion‐weighted magnetic resonance imaging (MRI) improves tissue characterization, staging, and response to treatment in cervical cancer .…”
mentioning
confidence: 99%